2022
DOI: 10.1177/20503121221118989
|View full text |Cite
|
Sign up to set email alerts
|

Compliance level and factors associated with iron–folic acid supplementation among pregnant women in Dangila, Northern Ethiopia: A cross-sectional study

Abstract: Objectives: Iron–folic acid non-compliance is a major problem in the study area. Therefore, this study aimed to assess the level of iron–folic acid supplementation compliance and associated factors among pregnant women. Methods: A community-based cross-sectional study design was conducted among pregnant women from 1 to 30 November 2018 in Dangila, Northern Ethiopia. A multi-stage sampling technique was used to select the participants. The data were collected using a structured questionnaire. For data entry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
3
8
1
Order By: Relevance
“…However, this result is lower compared with studies conducted in Mozambique (79%) 6 and northern Ethiopia (76.9%). 17 This difference could be due to geographic location, study period, sample size, and women's perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…However, this result is lower compared with studies conducted in Mozambique (79%) 6 and northern Ethiopia (76.9%). 17 This difference could be due to geographic location, study period, sample size, and women's perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the overall compliance rate of iron supplementation during pregnancy was found to be 92.4%. The current finding was higher than many previous reports in Ethiopia, such as the compliance rate, which varied from 60 to 63.6% in Addis Ababa 32 , 44 , 45 , 87.6% in Ethiopia 37 , Dire Dawa 46 , Shalla District 47 , 43.4% Dilla town 48 , 38.3% Hadassah 28 , 51.4% Burin district 49 , 52.9% Debbie 50 , 28.1% Denbiya District 36 , 28.7% Lay Armachiho 31 , 55% Gondar 51 , 47.6% Aykal town 30 , 44% Debre Tabor 52 , 43% Wollo 53 and 74.9% in four regions of Ethiopia 20 , 67.6% Simada district 54 , 52.8% Debay Tilat Gen district 55 , 37.2% Northwestern zone of Ethiopia 35 , 55.5% Debre Markos town 56 , 76.9% Dangila, Northern Ethiopia 57 , 40.9% in Adwa town 58 , and meta-analyses, 46.15, 46.1, 41.38 and 43.63% 59 62 . The present finding was also higher than many others, for example, a meta-analysis in SSA 63 , Uganda 64 , Kenya 65 , Nigeria 24 , Northwest Tanzania 66 , Northern Tanzania 67 , 22 sub-Saharan African countries 23 , Niger 68 , West Iran 69 , Cambodia 34 , Nepal 70 , 71 , India 72 , and Sri Lanka 73 .…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire initially prepared in English and then were translated to Afan Oromo and back into English. The questionnaire were pre-tested before implementation on twenty one (21) pregnant women attending ANC and using IFA supplement at Arsi Nagelle Health Center and revisions were made to the tool based on the results. One day of training was given to data collectors and supervisor on the objective of the study, data collection process, and relevance of the study to both data collectors and supervisors before actual data collection.…”
Section: Data Quality Assurancementioning
confidence: 99%
“…Studies conducted on Iron-folic in different parts of countries revealed that the adherence of Iron-folic among pregnant Mother ranged from 22.9% study conducted Mille and Assayita of Afar regional State to 76.9% study conducted on Dangila of Amhara regional state (1,3,6,(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation